Guarantees for the protection of the rights and legitimate interests of minor children and the spouse in need of divorce - Nukusheva, А.А.; Kudryavtseva, L.V.; Chervonaya, Y.A. (Bulletin of the Karaganda University “Law Series”, 2019)
In the article the actual and important aspect of family law, including international family law — the guarantee of protection of the rights and legitimate interests of minor children and needy spouse at divorce was considered. The purpose of this work is to identify the problematic elements of family divorce legislation in relation to guarantees, their legal features, stages of development and their relationship with the legislation of the Republic of Kazakhstan, Germany, France, the Russian Federation and some other states. The methodological basis of the work is the system approaches to the study of the theory, legal acts, which relate to the establishment of legal guarantees and ways to solve problems. In addition the methods of philosophical nature, analysis, synthesis, induction were implemented. The work was carried out with the help of dogmatic analysis, historical and normative, content and functional techniques. Based on the specifics of marriage, the legislator establishes guarantees for the protection of the rights and interests of family members in divorce, but some issues remain unresolved. In this regard, we analyze the legislation of foreign countries and propose ways to reform national law: to conclude bilateral international treaties to determine the jurisdiction, to establish new guarantees to protect the right of minor children to receive alimony, to reform the legislation on guardianship.